HISTORICAL LITERACY IN THE DIGITAL ERA: THE ROLE OF EDUCATORS IN DEVELOPING THE HISTORICAL THINKING SKILLS OF GRADE XI STUDENTS AT SMA NEGERI 2 PEMATANGSIANTAR - Asnewastri; Satria Chandra; Ahmad Fakhri Hutauruk; Andres M. Ginting; Jalatua Habungaran Hasugian; Syifa Asri Nadilla; Fajar Aditya (Academic Solution Publisher, 2026)
Teachers as stakeholders have a full role and responsibility for the sustainability of the school literacy movement. In this case, the teacher makes various efforts to maintain the school history literacy movement program. There are several efforts that can be made by teachers to develop and preserve the school literacy history movement, namely through planning the school literacy history movement and the school literacy movement process. The aims of this study were to: (1) determine the literacy skills of students in lesson planning for class XI at SMAN 2 Pematang Siantar (2) Knowing the teacher's role in fostering student literacy History in the learning process for class XI at SMAN 2 Pematang Siantar. The method used in this research is descriptive qualitative method, namely analyzing descriptive data by describing the results of the research that the researchers have done. This study uses data collection procedures are observation, interviews and documentation. The informants used were the principal, homeroom teacher, and class XI students. The results obtained in the literacy movement are the role of teachers at SMAN 2 Pematang Siantar carried out through planning and processes which are then implemented in the stages of habituation, development and learning.